Trade-off designs of power-to-methane systems via solid-oxide electrolyzer and the application to biogas upgrading. (1st August 2019) - Jeanmonod, Guillaume; Wang, Ligang; Diethelm, Stefan; Maréchal, François; Van herle, Jan
Highlights: Conceptual design of power-to-methane with air or oxygen sweep for biogas upgrading. Oxygen sweep by anode recirculation only marginally affects the system performance. Most biogas-upgrading systems behave similarly to the standalone power-to-methane. Internal methanation only beneficial at low voltage and high reactant utilization. Adverse effect of internal methane reforming reduced by high utilization and pressure. Abstract: Solid-oxide electrolyzer based power-to-methane is promising for large-scale energy storage as well as biogas upgrading by efficiently converting intermittent renewable power and CO2 (e.g., in biogas) into synthetic methane. Either air or pure oxygen can be employed in solid oxide electrolyzers for anode sweeping and thermal management. This work investigates the optimal conceptual design of a variety of power-to-methane layouts to (i) identify the effect of sweep-gas type on system performance and (ii) compare different concepts for biogas upgrading. Bi-objective optimization is performed to understand the trade-off between system efficiency and methane production with the effects of the key design variables. The results indicate that oxygen sweep only marginally affected the system performance (6% reduction in methane production at the same system efficiency). The methanation inside the electrolyzer helped achieve a higher system efficiency (over 90%) by maintaining the electrolyzer temperature as high as possible. Unlike most biogas-upgrading systems, which behaved similarly to the standalone power-to-methane system, with an efficiency range of 70–86%, the direct-biogas-electrolysis performed within a wide efficiency range (52–88%) and a reduced methane yield (50% less than the other systems operating at 70% efficiency). The detrimental methane reforming inside the electrolyzer was limited by increasing the reactant conversion and the electrolysis pressure. The various solid-oxide electrolyzer based power-to-methane concepts showed promising results for biogas upgrading applications. The practical choice of biogas-upgrading concepts will depend on the requirement of operational flexibility to handle variable renewable power considering different gas storage and carbon capture technologies.